2013
DOI: 10.1007/s00005-013-0222-5
|View full text |Cite
|
Sign up to set email alerts
|

The Dysfunction of NK Cells in Patients with Type 2 Diabetes and Colon Cancer

Abstract: Glucose metabolism disorders influence anticarcinogenic function of natural killer (NK) cells. The aim of this study was to evaluate the number and cytotoxic activity of NK cells in type 2 diabetic (T2D) patients with negative family history of cancer, type 2 diabetic subjects with newly diagnosed untreated colon cancer (T2DCC) and patients without type 2 diabetes with newly diagnosed, untreated colon cancer (CC). Incubation tests were performed in 18 T2D patients, treated with diet and oral antidiabetic agent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…Immunological abnormalities such as abnormal expression of NK cell surface markers and abnormal cytokine production may also be associated with the pathogenesis of DM. In fact, some researchers had reported decreased expression of NKp46 and changed levels of serum cytokines such as IFN‐γ, TNF‐α, TGF‐β, and VEGF in patients with DM . Recently, the relationship between immune response and metabolic diseases such as obesity, type 2 diabetes, and GDM was reported …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunological abnormalities such as abnormal expression of NK cell surface markers and abnormal cytokine production may also be associated with the pathogenesis of DM. In fact, some researchers had reported decreased expression of NKp46 and changed levels of serum cytokines such as IFN‐γ, TNF‐α, TGF‐β, and VEGF in patients with DM . Recently, the relationship between immune response and metabolic diseases such as obesity, type 2 diabetes, and GDM was reported …”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, NK cell cytotoxicity decreased in long‐standing type 1 DM group than that in the non‐DM healthy group . Patients with type 2 diabetes mellitus (DM) and impaired glucose tolerance (IGT) had also significantly lower levels of NK cell activity compared to that of the normal controls in both men and women . These reports prompted us to investigate the expression of pNK cell surface markers and the percentage of cytokine‐producing pNK cells in women with GDM.…”
Section: Discussionmentioning
confidence: 99%
“…Natural killer (NK) cells participate in innate immune responses and in animal models of T1D, it has been reported that depletion of NK cells prevents the development of T1D . An altered frequency of total number of NK cells has been found in LADA, but not in T2D, patients . Furthermore, it has been reported in children with T1D that NK cells have defects in signalling and function that might contribute to the pathogenesis of T1D .…”
Section: Introductionmentioning
confidence: 99%
“…Other proposed explanations for the increased risk include obesity-related insulin resistance (IR)[11] and cytokine production[12], which may directly influence CRC growth not only through promotion of angiogenesis[13,14], but also by inducing host inflammatory response[13,15] or decreasing natural killer (NK) lymphocyte cytotoxic activity and, thus, the immunological defense against cancer[16]. …”
Section: Introductionmentioning
confidence: 99%